Evaluation of Oracle NetSuite Adoption Using UTAUT Model at PT Austin Engineering Indonesia - Sri Zuliarni; Dwi Kartikasari (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
The purpose of this study is to evaluate the extent of acceptance and use of the Oracle NetSuite system at PT Austin Engineering Indonesia based on the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. In an effort to improve operational efficiency and effectiveness, many companies have begun to adopt cloud-based Enterprise Resource Planning (ERP) systems such as Oracle NetSuite. However, the success of its implementation is highly dependent on the level of acceptance from users. This study is a quantitative approach, involving 50 respondents taken through purposive sampling, namely active employees who use Oracle NetSuite. The questionnaire used was designed with a Likert scale of 1-5 and analyzed using SmartPLS software. The results of the analysis showed that Effort Expectancy and Facilitating Conditions had a significant influence on Behavioral Intention and Use Behavior. Meanwhile, Performance Expectancy and Social Influence did not show a significant influence on Behavioral Intention. The results of this study offer insights for the development of ERP technology adoption strategies in the corporate environment.